ANALISIS PENGARUH PAD, DAU, DAK, DAN DBH TERHADAP BELANJA LANGSUNG, SERTA DAMPAKNYA TERHADAP PERTUMBUHAN EKONOMI - Rizky, Ika Noer (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The study aims to determine the effect of Local revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH) to direct expenditure, as well as their impact on economic growth at the District/City in East Java. The method used in this research is quantitative with a population consisting of 38 Districts/City in East Java. The data used is data GDP at constant prices to see economic growth and local revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), Revenue Sharing Fund (DBH), and direct expenditure in the District/City East Java from 2010-2014. The data is sourced from the Directorate General of Fiscal Balance (DJPK) and the Central Statistics Agency East Java (BPS), as well as sources of other relevant financial data. Tests conducted by the path analysis (path analysis). The analysis of the first model showed that the partial revenue (PAD), General Allocation Fund (DAU), Revenue Sharing Fund (DBH) significantly affects direct expenditure. While the Special Allocation Fund (DAK) no significant effect on direct expenditure. The results of the analysis of the second model shows that the Local Revenue (PAD), Revenue Sharing Fund (DBH) and direct expenditure significantly affects economic growth, while the General Allocation Fund (DAU) and Special Allocation Fund (DAK) no significant effect on economic growth.Key Words : Local Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), Revenue Sharing FundÂ (DBH), Direct Expenditure, and Economic Growth.